Apolipoprotein A-I mimetic peptide reverses impaired arterial healing after injury by reducing oxidative stress. Issue 2 (August 2015) - Rosenbaum, Michael A.; Chaudhuri, Pinaki; Abelson, Benjamin; Cross, Brandy N.; Graham, Linda M.
Abstract: Objective: Endothelial cell (EC) migration is essential for healing of arterial injuries caused by angioplasty, but a high cholesterol diet inhibits endothelial repair. In vivo studies suggest that apolipoprotein A-I (apoA-I), the major protein constituent of HDL, is essential for normal healing of arterial injuries. ApoA-I mimetics, including 4F, have been designed to mimic the amphipathic portion of the apoA-I molecule. This study was undertaken to determine if 4F improves endothelial migration and healing. Methods: A razor scrape assay was used to analyze the effect of 4F on EC migration in vitro . Endothelial healing in vivo was assessed following electrical injury of carotid arteries in mice. Markers of oxidative stress were also examined. Results: Lipid oxidation products inhibited EC migration in vitro, but preincubation with L-4F preserved EC migration. Endothelial healing of carotid arterial injuries in mice on a high cholesterol diet was delayed compared with mice on a chow diet with 27.8% vs. 48.2% healing, respectively, at 5 days. Administration of D-4F improved endothelial healing in mice on a high cholesterol diet to 43.4%. D-4F administration had no effect on lipid levels but decreased markers of oxidation. In vivo, there was a significant inverse correlation between endothelial healing and plasma markers of oxidative stress. Conclusion: These studies suggested that an apoA-I mimetic can improve endothelial healing of arterial injuries by decreasing oxidative stress. Highlights: Hypercholesterolemia leads to increased oxidative stress and lipid oxidation. Increased oxidative stress impairs arterial healing after injury. L-4F improves endothelial migration in vitro in presence of oxidized lipids. D4-F improves endothelial healing after carotid injury in hypercholesterolemic mice. ApoA-I mimetics may reduce thrombogenicity and restenosis of angioplasty sites.